Erosion in gullies and impact on the chemical properties of soil and water (Research, Society and Development, 2020)
Environmental degradation involves several processes that influence the imbalance of an ecosystem, making it impossible to sustain life. In this work, the objective was to analyze the state of degradation and the characteristics of the soil and water of a erosion in gullie, located at the Instituto Federal Goiano - Campus Ceres - GO. The experiment was conducted by first determining the type of erosion and indicating the best applications for soil conservation. Chemical and physical analyzes of the soil were carried out using Embrapa methodology. The pH and total water hardness analyzes were performed according to FUNASA's practical water analysis manual. The study contributed to the recognition of the degradation of the area, in addition to assistance in other studies related to the characterization of soil and water properties. The local flow of water gradually silts the banks and the bottom of the erosion in gullie, causing sediment to the bed of the Rio Verde. The degraded area has good levels of soil nutrients, calcium and potassium stand out, but this pattern is associated with fertilizers carried constantly to gullies.